Exploring The Power of Social Communication on Tiktok Through a Qualitative Literature Review - Winda Pratiwi; Myanya Khintan Sabrina; Irmawan Rahyadi (Syntax Literate, 2022)
As the third-largest of the Big Five worldwide social networks, TikTok has rapidly gained global attention, attracting millions of users worldwide. The aim of this study is to explore the nuances and intricacies of social communication dynamics within the TikTok environment. This paper presents a comprehensive qualitative literature review that delves into the realm of social communication on TikTok by following a qualitative method of literature review, we have sorted 45 scientific journals from 3 sources: SAGE Journals, Wiley Journals, and Taylor & Francis Journals to support our phrase â€œSocial Communication on TikTokâ€. Through an in-depth analysis of relevant scholarly articles, this review highlights key themes, trends, and patterns that emerge from the literature. It examines the diverse forms of social communication on TikTok, including the creation and consumption of user-generated content, the role of influencers and trends, and the impact of TikTok on interpersonal relationships and societal norms. Moreover, this review sheds light on the social, cultural, and psychological implications of TikTok as a communication platform. By adopting a qualitative lens, this research provides a deeper understanding of how users engage, connect, and communicate on TikTok, offering valuable insights for researchers, practitioners, and policymakers in the field of social media and communication studies.